CIRI-CIRI BAHASA RUNNING TEXT PADA KABAR PAGI DI CHANNEL tvOne (THE LANGUAGE STYLE OF RUNNING TEXT IN KABAR PAGI ON tvOne CHANNEL) - Verawati, Eka; Wibisono, Bambang; Rochiyati S., A. Erna (Publika Budaya, 2014)
Running text is a short news report running continuously underneath of television screen during a certain programme. The function of running text is to make the audience get easier understanding from the information of some events happened, without directly seeing from the news programme or the stage. The rersearch ontends to describe and explain the use of diction, sentence pattern, and productivity of the sentence pattern of running text in Kabar Pagi news on tvOne channel. The result shows that there are four kinds of disctions within running text, those are origin verb, derived verbs which are separated from prefiks, abbreviation, and acronym. There are five kinds of sentence pattern used within running text, those are simple sentence, complex sentence, direct speech, invitation sentence, and special short sentence for sports. According to amount of sentence can be concluded that the most productive sentence pattern is the simple sentence. Key words: diction, sentence pattern, productivity of sentence pattern. ABSTRAK Running text adalah berita singkat yang berjalan pada tampilan bawah layar televisi secara berulang- ulang dalam suatu acara tertentu. Running text berfungsi untuk memudahkan pemirsa televisi memahami informasi dari beberapa peristiwa yang terjadi, tanpa menyaksikan langsung dari tempat kejadian atau dari tayangan acara berita televisi. Penelitian ini bertujuan mendeskripsikan dan menjelaskan penggunaan diksi, pola kalimat, dan keproduktivan pola kalimat running text pada acara Kabar Pagi di channel tvOne. Hasil penelitian menunjukkan dalam running text ada empat jenis diksi, yaitu verba asal, verba turunan yang mengalami pelepasan prefiks, singkatan, dan akronim. Pola kalimat yang digunakan dalam running text ada lima jenis, yaitu kalimat tunggal, kalimat majemuk, kalimat langsung, kalimat ajakan, dan kalimat singkat khusus bidang olahraga. Berdasarkan jumlah kalimat dapat disimpulkan pola kalimat yang paling produktif digunakan adalah kalimat tunggal. Kata kunci: diksi, pola kalimat, keproduktivan pola kalimat.